Nine Indonesian Populations of Leucaena leucochepala (Lam.) de Wit. for Wood-Energy Breeding versus var. Tarramba - Rina Laksmi Hendrati; Nur Hidayati (Jurnal Perbenihan Tanaman Hutan, 2018)
Renewable energy from fast-growing woody species needs to be initiated rapidly in Indonesia, facilitated with conducive climate for continuous growth. Selecting suitable species and exploring its populations to capture as wide variation as possible for successful screening, is required. Leucaena leucochepala, which is the wood has long  been used for wood-energy, has been grown widely in Indonesia. Growing for more than 50 generations since its introduction, it should have been very well adapted. This study is to evaluate early performances of its seedlings as genetic materials ready for its breeding. Seeds of ten populations from different regions and habitats have been collected as materials for energy-wood breeding, included var. Tarramba, the best world performer grown in Indonesia. Further, 80 families were selected as genetic materials for progeny test. L. leucochepala produce flowers in 4 ̶ 6 months, therefore evaluation of early growth at 3 months should be appropriate. Results show high variations among populations and families as well as among habitat promising for breeding success. Some Indonesian populations and families grow promisingly due to performing similarly  against var. Tarramba, even some families are better. By using 5 best families of 3 different habitats and compared to var. Tarramba, it shows that plants from Bali, collected from saline area, are as good as var. Tarramba’s, the world best performers.